The Role of Miftahul Huda Al-Ulya Sragen Islamic Boarding School in Strengthening Islamic Values Amidst Cultural Diversity - Kholil, Kholil; Sukari, Sukari (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the role of Pondok Pesantren Miftahul Huda Al-Ulya Sragen in strengthening Islamic values amidst cultural diversity. The pesantren serves as a gathering place for students and teachers from various regions of Indonesia, such as Aceh, NTT, Flores, and Java, each bringing their unique traditions. This research employs a library research method by analyzing various literature, documents, and references related to strengthening Islamic values and multiculturalism in pesantren. The findings reveal that the pesantren plays a vital role in teaching Islamic values such as tolerance, justice, and respect for cultural differences. However, challenges were identified in aligning these values, including resistance from conservative groups and the lack of systematic policy guidelines. As a solution, the integration of multiculturalism-based curricula and the enhancement of diversity awareness through learning activities are recommended. The study concludes that Pondok Pesantren Miftahul Huda Al-Ulya holds significant potential as an inclusive Islamic educational institution, not only reinforcing Islamic values but also fostering tolerance amidst the cultural diversity of its students.